Postmortem Burns Obfuscating the Objectives of Autopsy: An Autopsy Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
The autopsy surgeon plays a vital role in the investigation of a crime. His work importance mainly increases in the bodies which are brought dead, with no witnesses and no proper history. Many a times, scene of incidence, the inquest report, history and postmortem findings may not go hand-in-hand. In many homicides, fire is not an unusual method which is used to conceal a crime or to make deceased unrecognisable because of severe morphological and structural alterations caused by heat. Unidentified charred dead bodies pose a great challenge for forensic pathologists in commenting about the identity, ante mortem or postmortem burns and about the cause and manner of death. As the effects of heat on the body frequently cause complete or partial destruction of the body, autopsy of a severely burnt victim demands that postmortem heat-related changes be differentiated from antemortem trauma. Such burns are done in the perimortem period or when the victim have just died, making their diagnosis more difficult This article presents a case series of four concealed homicides where an attempt was made by the assailants to hide the murder by putting the dead body on fire. However, a clever and systematic forensic investigation revealed the true cause of death. This article stresses on the need of a detailed and thorough postmortem examination in such cases which appear pretty straight forward initially.
Keywords: Charred; Autopsy; Concealed homicide; Postmortem burns; Manner of death